Using PVM in the simulation of a hybrid dataflow architecture - Cavenaghi, M. A.; Spolon, R.; Perea-Martins, J. E.M.; Domingues, S. G.; Neto, A. Garcia (Springer Nature, 1996)
The aim of this work is to propose the migration of a hybrid dataflow architecture simulator developed on an uniprocessor system (sequential execution) to a multiprocessor system (parallel execution), using a message passing environment. To evaluate the communication between two process, we have been simulating an optical interconnection network based on WDM technics.